2016
DOI: 10.18355/pg.2016.5.2.311-319
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Validation of Scale of Motivation for Choosing Teaching as a Career Smvup3-S: Test-Retest Reliability and Iternal Integrity

Abstract: The study presents the results of research intended to verify time invariance of Scale of motivation for choosing teaching as a profession: SMVUP3-S (Tomsik -Veresova, 2016). SMVUP3-S is self-assessment scale that detects degree of representation of different types of motivation among prospective teachers (teacher trainee students). The research sample consisted of 52 Slovak university students from Constantine the Philosopher University in Nitra. Retest was administered to students after 50 to 70 days. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Indicators of empirical validity of this model are also researches carried out using SMVUP-4-S scale (and its reeditions). The following research facts were found with the use of this scale: gender differences (Tomšik, 2015), the differences with regard to study programs (Tomšik & Čerešník, 2017), demographic and geographical differences (Tomšik, 2016d), correlation with the questionnaire NEO-FFI (Tomšik & Gatial, 2018;Tomšik, 2018a), and DZSV questionnaire (Tomšik, 2018b), satisfaction with the choice of profession (Tomšik, 2016b) and time-dependent reliability was also investigated and satisfactory results were found (Tomšik, 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indicators of empirical validity of this model are also researches carried out using SMVUP-4-S scale (and its reeditions). The following research facts were found with the use of this scale: gender differences (Tomšik, 2015), the differences with regard to study programs (Tomšik & Čerešník, 2017), demographic and geographical differences (Tomšik, 2016d), correlation with the questionnaire NEO-FFI (Tomšik & Gatial, 2018;Tomšik, 2018a), and DZSV questionnaire (Tomšik, 2018b), satisfaction with the choice of profession (Tomšik, 2016b) and time-dependent reliability was also investigated and satisfactory results were found (Tomšik, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Following the agreement of the authors of the Fit-Choice model, the scale was translated into Slovak language and subsequently translated by different translators into English. Based on several validations (Tomšik & Verešová, 2015;Tomšik, 2016a, Tomšik, 2016c of the internal consistency and validity of the model, the final, fourth re-edition of the SMVUP model was developed for the teacher trainee students. This model consists of three scales that are saturated with the following factors:…”
Section: Instrument and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…87 Slovak first-year university students (42 male, 42 female, 3 uncategorized) aged from 18 to 20 years (M = 19.10) served as test participants, selected by random sampling. At the beginning of the students՚ first year in the TEFL program, their motivation was measured by the SMVUP (Tomsik, 2016a), which took 45-50 minutes to complete. The scale was administered and evaluated by a psychologist (one of the authors).…”
Section: Objectivesmentioning
confidence: 99%
“…However, the Fit-Choice Scale application in the Slovak Republic was not successful (Tomsik, 2016c). Therefore, the Scale of Motivation for Choosing teaching as a Profession (SMVUP) model has been developed (Tomsik, 2016a), aiming at a more comprehensive and valid examination of the motivation for choosing to teach in the Slovak Republic. The items in this tool were adapted to Slovak socio-cultural and educational specifics and adjusted to the Central European context.…”
Section: Introductionmentioning
confidence: 99%